2013
DOI: 10.1007/s13197-013-1114-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slaughter methods on the quality of Chilean jack mackerel (Trachurus murphyi) during refrigerated storage

Abstract: The main objective of this study was to assess the influence of slaughter methods on the quality of Chilean jack mackerel (Trachurus murphyi) during refrigerated storage on board. Fishes were slaughtered by asphyxia in air (AA), asphyxia in ice water (AI) or stunning fish heads (SH), and the rigor mortis, pH, total volatile basic nitrogen (TVB-N), trimethylamine (TMA), 2-thiobarbituric acid reactive substances (TBARS) and sensory properties for the fishes were analyzed. On day 0, Chilean jack mackerel samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Mergen & Geraldo Junior (2021) highlighted that thermonarcosis is one of the most used methods, in which different fish species are kept in a stunning tank for 15 min before bleeding. Similarly, for mackerel (Trachurus murphyi), Lyu et al (2015) observed a stunning time of 15 min. Pedrazzani et al (2009), when comparing the effect of two stunning methods (marrow section and thermonarcosis) on the well-being of Nile tilapia, found that the animals subjected to thermonarcosis were stunned at an average time of 750 s, which was 2 min and 52 s longer than the longest time recorded in the present study.…”
Section: Resultsmentioning
confidence: 91%
“…Mergen & Geraldo Junior (2021) highlighted that thermonarcosis is one of the most used methods, in which different fish species are kept in a stunning tank for 15 min before bleeding. Similarly, for mackerel (Trachurus murphyi), Lyu et al (2015) observed a stunning time of 15 min. Pedrazzani et al (2009), when comparing the effect of two stunning methods (marrow section and thermonarcosis) on the well-being of Nile tilapia, found that the animals subjected to thermonarcosis were stunned at an average time of 750 s, which was 2 min and 52 s longer than the longest time recorded in the present study.…”
Section: Resultsmentioning
confidence: 91%
“…The methods of catching, processing, storing, processing are of great importance for the final result of fish products. As a result, it was concluded that the protein source has a significant potential to meet human needs [30,31,32].…”
Section: сApture Fisheriesmentioning
confidence: 99%
“…Nevertheless, the methods of catch, processing and storage directly influence the pH values from fish (Aursand et al, 2009;Carneiro et al, 2013;Esaiassen et al, 2004;Gökoğlu & Yerlikaya, 2015;Karl, Lehmann, Rehbein, & Schubring, 2010;Lopes et al, 2004;Lyu, Huang, Liu, Zhou, & Ding, 2015;Rebouças, Rodrigues, Castro, & Vieira, 2012). The catching method significantly affected the pH during ice storage of Rutilus kutum in which the pH from fish caught by beach seine was lower than the pH of fish caught by gillnet (Raoofi et al, 2015).…”
Section: Hydrogen Potentialmentioning
confidence: 99%
“…The catching method significantly affected the pH during ice storage of Rutilus kutum in which the pH from fish caught by beach seine was lower than the pH of fish caught by gillnet (Raoofi et al, 2015). Regarding processing, the asphyxia in ice water method for slaughtering fish resulted in a higher pH and consequently exhibited a delayed rigor mortis, whereas the fish slaughtered by the stunning fish heads and asphyxia in air methods entered more rapidly into rigor mortis (Lyu et al, 2015). In addition, the type of raw materials also influences the pH values.…”
Section: Hydrogen Potentialmentioning
confidence: 99%